Labor Absorption and the Growth of Agricultural Output: A Simultaneous Spatial Durbin Panel Data Model Perspective of Fiscal Decentralization’s Impact in Indonesia - MUSTAQIM, MUSTAQIM; SETIAWAN, SETIAWAN; SUHARTONO, SUHARTONO; ULAMA, Brodjol Sutijo Suprih (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019, 2019)
This study aims to examine the empirical and short-term relationship between the implementation of fiscal decentralization policies and employment in Indonesia during the period from 2007-2015. We observe the impact of local government policies during the decentralization period through regional fiscal policy instruments, using the simultaneous equation of spatial Durbin panel data with the GMM approach. Significant changes that were expected from the post-centralization era after 1.5 decades of this policy have not been seen. Our main findings document that fiscal decentralization has not yet had a positive effect on employment and the agricultural sector’s production.